2020
DOI: 10.3389/fbioe.2020.00965
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism-Driven Metabolic Engineering for Bio-Based Production of Free R-Lipoic Acid in Saccharomyces cerevisiae Mitochondria

Abstract: Lipoic acid is a valuable organosulfur compound used as an antioxidant for dietary supplementation, and potentially anti-diabetic and anti-cancer. Currently, lipoic acid is obtained mainly through chemical synthesis, which requires toxic reagents and organic solvents, thus causing environmental issues. Moreover, chemically synthesized lipoic acid is conventionally a racemic mixture. To obtain enantiomerically pure R-lipoic acid, which has superior bioactivity than the S form, chiral resolution and asymmetric s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…To benefit from the substantial acetyl-CoA pool in the mitochondria for α-bisabolene production, the target pathway enzymes were fused with an N-terminus 26-amino-acid MLS that originated from subunit IV of the cytochrome oxidase (CoxIV) in S. cerevisiae, which is typically cleaved off upon entry into the mitochondrial matrix . To verify the subcellular targeting capability of the MLS in Y.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To benefit from the substantial acetyl-CoA pool in the mitochondria for α-bisabolene production, the target pathway enzymes were fused with an N-terminus 26-amino-acid MLS that originated from subunit IV of the cytochrome oxidase (CoxIV) in S. cerevisiae, which is typically cleaved off upon entry into the mitochondrial matrix . To verify the subcellular targeting capability of the MLS in Y.…”
Section: Resultsmentioning
confidence: 99%
“…19 To benefit from the substantial acetyl-CoA pool in the mitochondria for α-bisabolene production, the target pathway enzymes were fused with an N-terminus 26-aminoacid MLS that originated from subunit IV of the cytochrome oxidase (CoxIV) in S. cerevisiae, which is typically cleaved off upon entry into the mitochondrial matrix. 5 To verify the subcellular targeting capability of the MLS in Y. lipolytica, fluorescence microscopy was carried out to observe the fluorescence distribution in the yeast strains. By applying a mitochondrion-specific dye "MitoTracker Red" as a reference, the overlap of the red fluorescence signal from the dye with the green fluorescence signal from the MLS-tagged GFP in Po1g MLS-GFP confirmed that the MLS successfully translocated the GFP to the mitochondria (Figure 2).…”
Section: Compartmentalization Of the α-Bisabolenementioning
confidence: 99%
See 1 more Smart Citation
“…The membrane was incubated for 1 h in blocking buffer (0.5% non-fat dry milk) in TBS buffer containing 0.1% Tween 20 (TBST), washed three times for 10 min in TBST buffer, and incubated overnight at 4 • C with an HRP conjugated anti-HIS antibody diluted by 1:1000 (Thermo Fisher Scientific, MA, USA) in TBST buffer. [45] The membrane was washed for three times using TBST buffer and developed using the Signal Fire ECL reagent (Cell Signaling Technology, MA, USA).…”
Section: Gvp Production and Western Blot Analysismentioning
confidence: 99%
“…There are distinct studies demonstrating the effectiveness of using only the natural (active) form of ALA 11–14 . In this sense, the development of asymmetric synthetic protocols is imperative to access this goal 15–17 …”
Section: Introductionmentioning
confidence: 99%